A high-resistivity stable nickel-chromium alloy material and its preparation method
Patent Information
- Application Number
- CN202611056135.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-09-01
AI Technical Summary
[0006]为了克服上述现有技术的缺点,本发明的目的在于提供了一种高电阻稳定性镍铬合金材料及其制备方法,改善了传统镍铬合金在长期高温通电条件下易发生电阻漂移、晶粒粗化、氧化膜稳定性不足及析出相粗化的问题,从而提高合金材料的电阻稳定性、抗氧化性能、组织热稳定性和服役可靠性
[0035] (1) This invention introduces Y2O3-ZrO2 composite nano-oxide particles into the Ni-Cr-Al alloy matrix, which are dispersed and embedded in the matrix during mechanical alloying and hot pressing sintering. This can pin dislocation movement, grain boundary migration and high-temperature grain growth, thereby improving the microstructure stability and electrical stability of the alloy during long-term high-temperature service.
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrothermal alloy materials technology, specifically to a high-resistivity stable nickel-chromium alloy material and its preparation method. Background Technology
[0002] Nickel-chromium alloys are a class of electrothermal alloy materials with nickel and chromium as the main constituent elements. They possess high resistivity, good heat resistance, oxidation resistance, and processing and forming properties, and are widely used in heating wires, resistance strips, resistance sheets, industrial electric furnace heating elements, household electric heating devices, and high-temperature resistance elements. During the service life of electrothermal elements, the materials are typically subjected to long-term high-temperature, electrically energized, oxidizing atmospheres, and repeated thermal cycling environments. The stability of their resistivity, the stability of their surface oxide film, their microstructure stability, and their high-temperature strength directly affect heating efficiency, temperature control accuracy, and service life.
[0003] Existing nickel-chromium heating alloys typically improve their oxidation resistance by increasing the Cr content to form a protective Cr2O3 oxide film. Simultaneously, the addition of elements such as Al, Si, and Mn adjusts the alloy resistivity, improves oxide film adhesion, and enhances high-temperature performance. While these alloys can meet the application requirements of general heating elements under normal operating conditions, they still exhibit problems such as resistance drift, oxide film cracking and peeling, grain coarsening, and decreased mechanical properties under higher temperatures, longer operating times, or precise temperature control scenarios.
[0004] Furthermore, traditional nickel-chromium alloys are mostly prepared using processes such as vacuum melting, casting, forging, and annealing. Although these processes are mature, their ability to uniformly control nanoscale reinforcing phases and fine precipitates is limited. If performance is improved solely by conventional microalloying elements, the reinforcing phase tends to segregate at grain boundaries or in localized areas, making it difficult to form a stable, fine, and dispersed reinforcing structure. If the precipitates are too large or unevenly distributed, they not only fail to effectively hinder grain boundary migration but may also become stress concentration points, reducing the material's thermal cycling stability and high-temperature reliability.
[0005] Therefore, there is an urgent need to provide a new high-resistivity nickel-chromium alloy material and its preparation method. By combining alloy composition design, the introduction of composite nano-oxide dispersion, microalloying precipitation strengthening, and solid solution-hierarchical aging microstructure control, a uniform and stable composite nanophase structure can be constructed in the nickel-chromium alloy matrix, thereby improving the alloy's resistance stability, oxidation resistance, and service reliability under long-term energization, high-temperature oxidation, and thermal cycling conditions. Summary of the Invention
[0006] In order to overcome the shortcomings of the prior art, the present invention aims to provide a high-resistivity nickel-chromium alloy material and its preparation method, which improves the problems of resistance drift, grain coarsening, insufficient oxide film stability and coarsening of precipitates that traditional nickel-chromium alloys are prone to under long-term high-temperature energization conditions, thereby improving the resistance stability, oxidation resistance, thermal stability and service reliability of the alloy material.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a high-resistivity-stability nickel-chromium alloy material, comprising a nickel-chromium alloy matrix and a composite nanophase dispersed in the nickel-chromium alloy matrix;
[0008] Based on the mass percentage of the nickel-chromium alloy matrix, the chemical composition of the nickel-chromium alloy matrix is as follows: Cr 18-22%, Al 2.5-4.5%, Mn 1.0-2.0%, Si 0.5-1.5%, Nb 0.3-0.8%, Zr 0.05-0.25%, Y 0.01-0.08%, C 0.02-0.06%, N 0.01-0.03%, S≤0.002%, P≤0.003%, with the balance being Ni and unavoidable impurities;
[0009] Based on the total mass of the nickel-chromium alloy material, the composite nanophase includes 0.10–0.50% Y2O3-ZrO2 composite nano-oxide particles, as well as Nb, Zr composite carbides and Ni3Al intermetallic compound precipitates in the matrix.
[0010] Furthermore, the Nb, Zr composite carbide is (Nb, Zr)C nanocarbide with an average particle size of 5-30 nm;
[0011] The average particle size of the Ni3Al intermetallic compound precipitate is 20–80 nm.
[0012] The total integral number of the composite nanophase in the nickel-chromium alloy matrix is 2 to 6%.
[0013] Furthermore, the average particle size of the Y2O3-ZrO2 composite nano-oxide particles is 8-30 nm, and the mass ratio of Y2O3 to ZrO2 is 1:0.5-0.8.
[0014] Furthermore, the preparation method of high-resistivity stable nickel-chromium alloy material includes the following steps:
[0015] S1. Batching and Vacuum Induction Melting:
[0016] The nickel-chromium alloy matrix is prepared by batching and smelting in a vacuum induction furnace at a temperature of 1550-1600℃ and a vacuum degree of no more than 10Pa. After melting, Al-Ca composite deoxidizer is added for deoxidation treatment, and then it is cast into an electrode rod.
[0017] S2. Electroslag remelting:
[0018] The electrode rod obtained in step S1 is subjected to electroslag remelting. The electroslag remelting slag system includes CaF2, Al2O3 and CaO. The melting rate is controlled at 4-6 kg / min during the remelting process to obtain nickel-chromium alloy ingots.
[0019] S3. Powdering and Mechanical Alloying:
[0020] The nickel-chromium alloy ingot obtained in step S2 is crushed or milled into alloy powder, wherein the particle size of the alloy powder is 50-200 μm.
[0021] The alloy powder is mixed with Y2O3 nanopowder and ZrO2 nanopowder, and then subjected to high-energy ball milling under argon protection to disperse and embed the Y2O3-ZrO2 composite nano-oxide particles into the alloy powder.
[0022] S4. Hot pressing sintering and hot working:
[0023] The ball milled powder obtained in step S3 is hot-pressed and sintered in a vacuum or inert atmosphere at a temperature of 1150–1200°C and a pressure of 30–50 MPa.
[0024] After sintering, the alloy billet is forged and rolled at 1050-1100℃ with a total deformation of not less than 70%.
[0025] S5. Solution treatment and graded aging:
[0026] The alloy billet obtained in step S4 is solution treated at 1080–1120°C for 30–60 min and then rapidly cooled.
[0027] Then, the material undergoes graded aging treatment by holding it at 430–470℃ for 1–3 hours, at 500–540℃ for 3–5 hours, and at 560–600℃ for 1–3 hours in sequence, so that Nb, Zr composite carbides and Ni3Al precipitates are dispersedly precipitated, resulting in a high-resistivity stable nickel-chromium alloy material.
[0028] Furthermore, in step S1, the amount of Al-Ca composite deoxidizer added is 0.03 to 0.15% of the melt mass; the casting temperature after the vacuum induction melting is 1480 to 1520°C, and bottom pouring is adopted.
[0029] Further, in step S2, the electroslag remelting slag system comprises 50-65% CaF2, 20-35% Al2O3, and 10-20% CaO by mass percentage; the slag material is dried at 650-750℃ for 2-4 hours before electroslag remelting.
[0030] Further, in step S3, the total amount of Y2O3 nanopowder and ZrO2 nanopowder added is 0.10 to 0.50% of the alloy powder mass; the ball-to-material ratio of the high-energy ball mill is 10 to 20:1, and the ball milling time is 15 to 16 hours.
[0031] The high-energy ball milling is carried out using a stepped rotation speed: 250-350 rpm in the first stage, 350-450 rpm in the middle stage, and 200-300 rpm in the last stage; the machine is stopped and cooled for 10-20 minutes after each continuous ball milling for 0.5-1.5 hours.
[0032] Furthermore, in step S5, after the graded aging treatment, the alloy material after graded aging is held at 750-850°C for 0.5-2 hours and then furnace cooled to increase the proportion of low-energy grain boundaries and coherent twin boundaries in the alloy material and reduce the tendency of continuous precipitates at grain boundaries to form.
[0033] The grain boundary controlled annealing treatment is carried out under a strong magnetic field of 8-12T, with the magnetic field direction parallel to the rolling or drawing direction of the alloy material. The heating rate is 3-8℃ / min and the cooling rate is 1-3℃ / min.
[0034] Compared with the prior art, the present invention has the following beneficial technical effects:
[0035] (1) This invention introduces Y2O3-ZrO2 composite nano-oxide particles into the Ni-Cr-Al alloy matrix, which are dispersed and embedded in the matrix during mechanical alloying and hot pressing sintering. This can pin dislocation movement, grain boundary migration and high-temperature grain growth, thereby improving the microstructure stability and electrical stability of the alloy during long-term high-temperature service.
[0036] (2) The present invention uses the combination of Nb, Zr and C to form fine and dispersed (Nb,Zr)C nanocarbides in the alloy during the graded aging process; at the same time, Al and Ni are used to form Ni3Al intermetallic compound precipitates. The two work together to improve the matrix strength and high temperature creep resistance, and reduce the resistance fluctuation caused by microstructure coarsening.
[0037] (3) The present invention adopts a combination of vacuum induction melting and electroslag remelting, which can reduce the content of inclusions and harmful impurities and improve the uniformity of alloy composition; then, through powder making, mechanical alloying and hot pressing sintering processes, the composite nano phase is more evenly distributed in the alloy matrix, avoiding the problems of nanoparticle agglomeration and segregation in traditional melting processes.
[0038] (4) The present invention employs solution treatment and multi-stage graded aging treatment to allow different types of precipitates to nucleate, grow and remain fine and dispersed in sequence, which helps to reduce the tendency of continuous precipitation at grain boundaries, improve grain boundary stability, and thus improve the service reliability of the alloy under thermal cycling, long-term electrical and oxidizing environments. (5) The nickel-chromium alloy material obtained by the present invention has high resistivity, low resistance temperature drift, good oxidation resistance and long service life, and can be used in high-temperature electric heating elements, precision resistance materials, resistance strips, heating wires and industrial heating furnace components, and has good industrial application value. Detailed Implementation
[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Y2O3-ZrO2 composite nano-oxide particles: Y2O3 nanopowder and ZrO2 nanopowder are premixed at a mass ratio of 1:0.5-0.8, anhydrous ethanol is added as a dispersion medium, and ultrasonic dispersion is carried out for 40 min to obtain an oxide nanopowder dispersion; then dried at 60-80℃, ground and sieved.
[0041] The Y content in the nickel-chromium alloy matrix refers to the Y element content added to and dissolved or segregated in the matrix / grain boundary by metallic yttrium or yttrium master alloy; the Y in the Y2O3 nanopowder exists in the form of an oxide phase and is not included in the Y content in the chemical composition of the nickel-chromium alloy matrix.
[0042] The Al-Ca composite deoxidizer has a Ca mass fraction of 35%, with the balance being Al and unavoidable impurities.
[0043] The Y2O3 nanopowder used in this embodiment of the invention can be yttrium oxide nanopowder with a purity of not less than 99.9% and an average particle size of 50-100 nm, such as Y2O3 nanopowder with product code NCZ-RK-707 / 24, manufactured by Nanochemazone; the ZrO2 nanopowder used can be zirconium oxide nanopowder with a purity of not less than 99.9% and an average particle size of 50-100 nm, such as ZrO2 nanopowder with product code NCZ-RK-712 / 24, manufactured by Nanochemazone.
[0044] The Y2O3-ZrO2 composite nano-oxide particles refer to a group of composite oxide particles formed by high-energy ball milling of Y2O3 nanoparticles and ZrO2 nanoparticles, which have interfacial contact and are dispersed in a nickel-chromium alloy matrix.
[0045] Example 1
[0046] This embodiment provides a high-resistivity-stability nickel-chromium alloy material. By mass percentage, the nickel-chromium alloy matrix composition is: Cr 18.0%, Al 2.5%, Mn 1.0%, Si 0.5%, Nb 0.3%, Zr 0.05%, Y 0.01%, C 0.02%, N 0.01%, S≤0.002%, P≤0.003%, with the balance being Ni and unavoidable impurities.
[0047] The total amount of Y2O3 nanopowder and ZrO2 nanopowder added is 0.10% by weight of alloy powder, and the mass ratio of Y2O3 to ZrO2 is 1:0.5.
[0048] The preparation method of this embodiment includes the following steps:
[0049] S1. Batching and Vacuum Induction Melting: Weigh out nickel, chromium, aluminum, manganese, silicon, niobium, zirconium, yttrium and carbon source raw materials according to the above composition, and melt them in a vacuum induction furnace at a melting temperature of 1550℃ and a vacuum degree of 8Pa. After melting, add 0.03% of Al-Ca composite deoxidizer by mass of the melt for deoxidation treatment, and then cast the electrode rods by bottom pouring at 1480℃.
[0050] S2. Electroslag remelting: The electrode rod obtained in step S1 is subjected to electroslag remelting. The electroslag remelting slag system is CaF2 50%, Al2O3 35%, and CaO 15% by mass percentage. Before remelting, the slag material is dried at 650℃ for 2 hours. During the remelting process, the melting rate is controlled at 4 kg / min to obtain a nickel-chromium alloy ingot.
[0051] S3. Powdering and Mechanical Alloying: The nickel-chromium alloy ingot obtained in step S2 is crushed and milled into alloy powder with a particle size of 50-100 μm; the alloy powder is mixed with Y2O3 nanopowder and ZrO2 nanopowder, and high-energy ball milling is carried out under argon protection with a ball-to-material ratio of 10:1 and a total ball milling time of 15 h; the rotation speed is 250 rpm in the first stage, 350 rpm in the middle stage, and 200 rpm in the last stage. After each continuous ball milling for 1 h, the machine is stopped and cooled for 10 min to allow the Y2O3-ZrO2 composite nano-oxide particles to be dispersed and embedded in the alloy powder.
[0052] S4. Hot pressing sintering and hot working: The ball milled powder obtained in step S3 is hot pressed and sintered in a vacuum environment at a temperature of 1150℃ and a pressure of 30MPa; after sintering, it is forged and rolled at 1050℃ with a total deformation of 70% to obtain an alloy billet.
[0053] S5. Solution treatment and graded aging: The alloy billet obtained in step S4 was solution treated at 1080℃ for 30 min and then rapidly cooled; subsequently, it was subjected to graded aging treatment by holding at 430℃ for 1 h, 500℃ for 3 h, and 560℃ for 1 h in sequence, so that the (Nb,Zr)C nano carbides and Ni3Al intermetallic compound precipitates were dispersed; finally, it was held at 750℃ and 8T strong magnetic field for 0.5 h and then furnace cooled. The direction of the magnetic field was parallel to the rolling direction of the alloy. The heating rate was 3℃ / min and the cooling rate was 1℃ / min, so as to obtain a nickel-chromium alloy material with high resistance stability.
[0054] Example 2
[0055] This embodiment provides a high-resistivity-stability nickel-chromium alloy material. By mass percentage, the nickel-chromium alloy matrix composition is: Cr 20.0%, Al 3.5%, Mn 1.5%, Si 1.0%, Nb 0.55%, Zr 0.15%, Y 0.05%, C 0.04%, N 0.02%, S≤0.002%, P≤0.003%, with the balance being Ni and unavoidable impurities.
[0056] The total amount of Y2O3 nanopowder and ZrO2 nanopowder added is 0.30% by weight of alloy powder, and the mass ratio of Y2O3 to ZrO2 is 1:0.65.
[0057] The preparation method of this embodiment includes the following steps:
[0058] S1. Batching and Vacuum Induction Melting: Weigh the raw materials according to the above composition and melt them in a vacuum induction furnace at a melting temperature of 1580℃ and a vacuum degree of 5Pa. After melting, add 0.09% Al-Ca composite deoxidizer by mass of the melt for deoxidation treatment, and then cast the electrode rods by bottom pouring at 1500℃. S2. Electroslag Remelting: Remelt the electrode rods obtained in step S1 by electroslag remelting. The electroslag remelting slag system is CaF2 58%, Al2O3 27%, and CaO 15% by mass percentage. Before remelting, dry the slag at 700℃ for 3 hours. During the remelting process, control the melting rate at 5 kg / min to obtain nickel-chromium alloy ingots.
[0059] S3. Powdering and Mechanical Alloying: The nickel-chromium alloy ingot obtained in step S2 is crushed and milled into alloy powder with a particle size of 80-150 μm; the alloy powder is mixed with Y2O3 nanopowder and ZrO2 nanopowder, and high-energy ball milling is carried out under argon protection with a ball-to-material ratio of 15:1 and a total ball milling time of 15.5 h; the rotation speed is 300 rpm in the first stage, 400 rpm in the middle stage, and 250 rpm in the last stage. After each continuous ball milling for 1 h, the machine is stopped and cooled for 15 min to ensure that the composite nano-oxide particles are uniformly dispersed in the alloy powder.
[0060] S4. Hot pressing sintering and hot working: The ball milled powder obtained in step S3 is hot pressed sintered in a vacuum environment at a temperature of 1180℃ and a pressure of 40MPa; after sintering, it is forged and rolled at 1080℃ with a total deformation of 75% to obtain an alloy billet.
[0061] S5. Solution treatment and graded aging: The alloy billet obtained in step S4 was solution treated at 1100℃ for 45 min and then rapidly cooled; subsequently, it was graded aging treatment was performed by holding at 450℃ for 2 h, 520℃ for 4 h, and 580℃ for 2 h in sequence; finally, it was furnace cooled after holding at 800℃ and a 10T strong magnetic field for 1 h, with the magnetic field direction parallel to the alloy rolling direction, the heating rate being 5℃ / min, and the cooling rate being 2℃ / min, to obtain a high-resistance-stability nickel-chromium alloy material.
[0062] Example 3
[0063] This embodiment provides a high-resistivity-stability nickel-chromium alloy material. By mass percentage, the nickel-chromium alloy matrix composition is: Cr 22.0%, Al 4.5%, Mn 2.0%, Si 1.5%, Nb 0.8%, Zr 0.25%, Y 0.08%, C 0.06%, N 0.03%, S≤0.002%, P≤0.003%, with the balance being Ni and unavoidable impurities.
[0064] The total amount of Y2O3 nanopowder and ZrO2 nanopowder added is 0.50% by weight of alloy powder, and the mass ratio of Y2O3 to ZrO2 is 1:0.8.
[0065] The preparation method of this embodiment includes the following steps:
[0066] S1. Batching and Vacuum Induction Melting: Weigh the raw materials according to the above composition and melt them in a vacuum induction furnace at a melting temperature of 1600℃ and a vacuum degree of 2Pa. After melting, add 0.15% Al-Ca composite deoxidizer by mass of the melt for deoxidation treatment, and then cast the electrode rods by bottom pouring at 1520℃. S2. Electroslag Remelting: Remelt the electrode rods obtained in step S1 by electroslag remelting. The electroslag remelting slag system is composed of CaF2 65%, Al2O3 20%, and CaO 15% by mass percentage. Before remelting, dry the slag at 750℃ for 4 hours. During the remelting process, control the melting rate at 6 kg / min to obtain nickel-chromium alloy ingots.
[0067] S3. Powdering and Mechanical Alloying: The nickel-chromium alloy ingot obtained in step S2 is crushed and milled into alloy powder with a particle size of 100-200 μm; the alloy powder is mixed with Y2O3 nanopowder and ZrO2 nanopowder, and high-energy ball milling is carried out under argon protection with a ball-to-material ratio of 20:1 and a total ball milling time of 16 h; the rotation speed is 350 rpm in the first stage, 450 rpm in the middle stage, and 300 rpm in the last stage. After each 0.5 h of continuous ball milling, the machine is stopped and cooled for 20 min to allow the Y2O3-ZrO2 composite nano-oxide particles to be fully dispersed and embedded in the alloy powder.
[0068] S4. Hot pressing sintering and hot working: The ball milled powder obtained in step S3 is hot pressed sintered in a vacuum environment at a temperature of 1200℃ and a pressure of 50MPa; after sintering, it is forged and rolled at 1100℃ with a total deformation of 80% to obtain an alloy billet.
[0069] S5. Solution treatment and graded aging: The alloy billet obtained in step S4 was solution treated at 1120℃ for 60 min and then rapidly cooled; subsequently, it was graded aging treatment was performed by holding at 470℃ for 3 h, 540℃ for 5 h, and 600℃ for 3 h in sequence to fully disperse the (Nb,Zr)C nanocarbides and Ni3Al intermetallic compound precipitates; finally, it was furnace cooled after holding at 850℃ and a strong magnetic field of 12T for 2 h, with the magnetic field direction parallel to the alloy rolling direction, the heating rate being 8℃ / min, and the cooling rate being 3℃ / min, to obtain a high-resistivity stable nickel-chromium alloy material.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 3 is that Y2O3 nanopowder and ZrO2 nanopowder are not added in step S3. Only the nickel-chromium alloy powder is subjected to high-energy ball milling under the same ball-to-material ratio, the same ball milling time and the same rotation speed. The other alloy composition and preparation steps are the same as in Example 3.
[0072] Since Y2O3-ZrO2 composite nano-oxide particles were not introduced in this comparative example, the alloy matrix lacks stable and dispersed nano-pinned phases. This weakens the inhibitory effect on grain boundary migration and grain growth during subsequent hot working, solution treatment and aging processes, and makes it easier for grain coarsening and resistance drift to occur under long-term high-temperature energized conditions.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 3 is that the electroslag remelting process in step S2 is omitted. Instead, the electrode rod obtained by vacuum induction melting and casting in step S1 is directly crushed or milled into alloy powder, and then powdering and mechanical alloying, hot pressing sintering, hot working, solution treatment and graded aging treatment are carried out. All other parameters are the same as in Example 3.
[0075] Since this comparative example did not undergo electroslag remelting and refining, the inclusions, harmful impurities, and local component segregation in the alloy could not be further reduced, which may lead to a decrease in the purity and microstructure uniformity of the subsequent mechanical alloying powder, thereby affecting the uniform distribution of the composite nanophase and the oxidation resistance and electrical stability of the alloy material.
[0076] Comparative Example 3
[0077] The difference between this comparative example and Example 3 is that the three-stage graded aging treatment and the strong magnetic field grain boundary controlled annealing treatment are not performed in step S5. Specifically, the alloy billet obtained in step S4 is solution treated at 1120°C for 60 min and then rapidly cooled, and then aged at 520°C for 4 h in a single stage and then air-cooled. The remaining alloy composition and preparation steps are the same as in Example 3.
[0078] Because this comparative example did not employ a graded aging process, the Nb, Zr composite carbides and Ni3Al intermetallic compound precipitates were difficult to precipitate in a fine, dispersed and uniform manner at different temperature stages, which easily led to problems such as insufficient quantity of precipitates, uneven size or local coarsening. At the same time, the lack of strong magnetic field grain boundary control annealing treatment resulted in insufficient improvement in grain boundary stability, and the alloy microstructure stability was relatively poor under long-term thermal cycling and high-temperature energization conditions.
[0079] Comparative Example 4
[0080] The difference between this comparative example and Example 3 is that the total amount of Y2O3 nanopowder and ZrO2 nanopowder added in step S3 is increased to 0.80%, while the mass ratio of Y2O3 to ZrO2 remains 1:0.8; the remaining alloy composition and preparation steps are the same as in Example 3.
[0081] Because the amount of composite nano-oxide particles added in this comparative example was too high, exceeding the reasonable dispersion strengthening range, nanoparticle agglomeration zones were easily formed during ball milling and sintering, leading to localized stress concentration and uneven microstructure. Although excessive oxide particles can improve grain boundary pinning to a certain extent, they reduce matrix continuity and hot working uniformity, adversely affecting the alloy's thermal cycling stability, processing performance, and electrical resistance uniformity.
[0082] 1. Chemical composition testing
[0083] The contents of metallic elements such as Cr, Al, Mn, Si, Nb, Zr, Y, and Ni in the alloy were determined using inductively coupled plasma atomic emission spectrometry (ICP-AES) or photoelectric direct-reading spectrometry (PDS-AES). The contents of elements such as C, S, N, and O were determined using a carbon-sulfur analyzer and an oxygen-nitrogen analyzer. During the testing process, the sample surface should be cleaned of oxide scale, oil, and processing contaminants to ensure that the test results accurately reflect the composition of the alloy matrix.
[0084] 2. Resistivity and Temperature Coefficient of Resistance Test
[0085] Resistivity, temperature coefficient of resistance, and resistance stability were tested according to GB / T1234-2012 "High Resistance Heating Alloys". Each group of samples was processed into wire or strip specimens, and the room temperature resistance was measured using the four-terminal method. Resistance changes were measured at different temperature points, and the resistivity at 20℃ and the temperature coefficient of resistance in the range of 20–900℃ were calculated. The resistance change rate after long-term energization was compared using the same specimen size and the same test method.
[0086] 3. Microscopic tissue testing
[0087] Microstructure observation was performed in accordance with GB / T13298-2015 "Methods for Examination of Microstructure of Metals". After cutting, mounting, grinding, polishing and etching, the alloy samples were observed with a metallographic microscope or scanning electron microscope to observe the grain morphology, inclusion distribution, precipitate distribution and oxide film cross-sectional morphology.
[0088] 4. Average grain size test
[0089] The average grain size was tested according to GB / T6394-2017 "Method for Determination of Average Grain Size of Metals". At least 5 fields of view were randomly selected for each sample group for statistical analysis, and the average grain size was calculated to evaluate the inhibitory effect of composite nanoparticles on grain boundary migration and grain growth.
[0090] 5. Nanoscale precipitate particle size test
[0091] The particle size and distribution of Y2O3-ZrO2 composite nano-oxide particles, (Nb,Zr)C nano-carbide, and Ni3Al intermetallic compound precipitates were observed and analyzed using transmission electron microscopy. At least five fields of view were selected for each sample group, and at least 50 particles were counted in each field of view to calculate the average particle size.
[0092] 6. Antioxidant performance test
[0093] The oxidation resistance test was conducted according to HB5258-2000 "Test Method for Determination of Oxidation Resistance of Steel and High-Temperature Alloys". The sample was processed into a sheet, and after grinding, cleaning, drying and weighing, it was kept at 1000℃ in air atmosphere for 100h. The mass change before and after oxidation was tested, and the weight gain per unit area was calculated to evaluate the density and stability of the oxide film on the alloy surface.
[0094] 7. Thermal cycling stability test
[0095] Thermal cycling stability testing was conducted using a high-temperature box-type resistance furnace. Each group of samples was processed into 20mm × 10mm × 2mm sheet specimens, with three parallel samples per group. Before the test, the specimen surfaces were sequentially polished with 400#, 800#, and 1200# sandpaper to remove oxide scale and machining scratches, then ultrasonically cleaned with anhydrous ethanol for 5 minutes, and dried in an 80℃ oven for 30 minutes. After drying, the specimen dimensions were measured, and the initial room temperature resistivity R0 was determined using the four-terminal method.
[0096] During testing, the sample was placed in an alumina crucible and then placed in a box-type resistance furnace. The temperature was raised from room temperature to 900°C in an air atmosphere at a rate of 10°C / min. Once the furnace temperature reached 900°C, it was held for 10 minutes to ensure the sample was fully heated and completed one high-temperature oxidation process. The sample was then removed from the furnace and allowed to cool naturally in air to 25–35°C, which was counted as one thermal cycle. This heating, holding, and air-cooling process was repeated 300 times.
[0097] During the thermal cycling process, the sample was removed and observed after every 50 cycles, and the presence of oxide film cracking, peeling, flaking, flaking, or significant discoloration was recorded. After 300 cycles, the sample was cooled to room temperature, and surface dust was gently removed with a soft brush without mechanical polishing. The room temperature resistance R1 after thermal cycling was then measured using the four-terminal method. The rate of change of resistance after thermal cycling was calculated using the following formula:
[0098] ΔR1=[(R1-R0) / R0]×100%
[0099] In the formula, ΔR1 is the rate of change of resistance after thermal cycling, in %; R0 is the room temperature resistance of the sample before thermal cycling, in Ω; and R1 is the room temperature resistance of the sample after 300 thermal cycles, in Ω. The smaller the rate of change of resistance after thermal cycling, and the less severe the cracking and peeling of the oxide film, the better the microstructure stability, oxide film adhesion, and resistance stability of the alloy under repeated heating and cooling conditions.
[0100] 8. Long-term power-on stability test
[0101] Long-term electrical stability testing was conducted using a self-made high-temperature electrical aging device. Each group of samples was processed into wire specimens with a diameter of 1.0 mm and a length of 300 mm, with three parallel samples per group. Before testing, the wire was held at 800℃ for 30 minutes and then cooled in the furnace to eliminate residual stress generated during winding and processing. The wire was then wound into a spiral heating element with an outer diameter of 25 mm, a pitch of 3 mm, and 10 effective turns, with 30 mm reserved at both ends for wiring. The winding dimensions, effective heating length, and wiring method were ensured to be consistent across all groups of samples.
[0102] Before the test, the initial resistance value R0 of each spiral heating element at 20℃ was determined using the four-terminal method. During the test, the spiral heating elements were placed horizontally on a high-temperature resistant alumina support and installed in an air atmosphere high-temperature furnace, connected to an adjustable DC power supply or an AC regulated power supply. By adjusting the input voltage and current, the sample was energized and heated to 900℃, and the temperature of the heating zone of the sample was monitored using a thermocouple or infrared thermometer. The temperature was controlled within the range of 900±10℃ during the test.
[0103] The samples were continuously aged at 900℃ for 1000 hours. During the aging process, the power was stopped every 100 hours, and the samples were allowed to cool to room temperature with the furnace or air. The room temperature resistance was then measured using the four-terminal method, and the resistance change was recorded. After the measurement was completed, the power was turned on again to raise the temperature for the next stage of aging. During the test, the samples were observed for phenomena such as localized ablation, wire breakage, peeling of the surface oxide film, spiral deformation, or loose terminals.
[0104] After continuous energization for 1000 hours, the sample was allowed to cool to room temperature, and the final room temperature resistance value Rt was measured again. The rate of change of resistance after long-term energization was calculated using the following formula:
[0105] ΔR2=[(Rt-R0) / R0]×100%
[0106] In the formula, ΔR2 is the resistance change rate after long-term energization, in %; R0 is the room temperature resistance value of the sample before aging, in Ω; and Rt is the room temperature resistance value of the sample after continuous energization at 900℃ for 1000h, in Ω. The smaller the resistance change rate, the smaller the resistance drift of the alloy under long-term high-temperature energized service conditions, and the better the microstructure stability and service reliability.
[0107] 9. Room temperature mechanical property testing
[0108] The room temperature tensile properties were tested in accordance with GB / T228.1-2021 "Metallic materials, tensile testing—Part 1: Test at room temperature". The specimens were processed into standard tensile specimens, and the room temperature tensile strength and elongation after fracture were determined to evaluate the processing performance and room temperature mechanical properties of the alloy materials.
[0109] 10. High-temperature mechanical property testing
[0110] The high-temperature tensile properties test was conducted in accordance with GB / T228.2-2015 "Metallic materials - Tensile testing - Part 2: High-temperature test method". The test temperature was set to 900℃. After the sample was heated to the set temperature and held at that temperature for stabilization, the tensile test was performed. The tensile strength at 900℃ and the elongation after fracture at 900℃ were measured to evaluate the mechanical stability of the alloy material under high-temperature service conditions.
[0111] Table 1: Microstructure Tests
[0112] Example 1 20.8 17.8 50.6 4.2 16.6 Example 2 18.9 16.4 48.7 4.5 15.4 Example 3 17.6 15.6 46.2 4.8 14.7 Comparative Example 1 Not detected 18.6 49.8 3.4 22.8 Comparative Example 2 19.7 17.1 50.2 4.2 20.5 Comparative Example 3 18.5 25.8 70.6 3.7 21.6 Comparative Example 4 30.4 15.9 47.5 5.9 18.8
[0113] As shown in Table 1, in Examples 1-3, the Y2O3-ZrO2 composite nano-oxide, (Nb,Zr)C nano-carbide, and Ni3Al precipitates all maintained a fine and dispersed distribution, and the average grain size of the alloy remained at a low level. This indicates that the mechanical alloying, hot pressing sintering, graded aging, and grain boundary controlled annealing processes employed in this invention can effectively suppress grain growth and coarsening of precipitates. The microstructure parameters of Examples 1-3 showed little difference, with Example 3 exhibiting the best microstructure refinement effect due to a better match between the amount of composite nano-oxide added, the ball milling regime, and the aging regime.
[0114] Comparative Example 1, without the addition of Y2O3-ZrO2 composite nano-oxides, lacked the constraint effect of nano-pinning on grain boundaries, resulting in an increase in average grain size to 22.8 μm. Comparative Example 2, by omitting the electroslag remelting process, saw a decrease in the control effect of alloy inclusions and compositional segregation, leading to an increase in grain size and a reduction in microstructure uniformity. Comparative Example 3, without the use of three-stage graded aging and strong magnetic field grain boundary controlled annealing, showed significant coarsening of (Nb,Zr)C carbides and Ni3Al precipitates. In Comparative Example 4, the amount of composite nano-oxides added was too high, causing some nanoparticles to agglomerate, resulting in an increase in the average particle size of the oxides. Although the grain size was still somewhat controlled, the microstructure uniformity decreased.
[0115] Table 2: Resistance Stability and Antioxidant Performance Tests
[0116] Example 1 1.21 112 0.53 0.50 0.75 Example 2 1.22 106 0.48 0.46 0.68 Example 3 1.24 101 0.44 0.43 0.62 Comparative Example 1 1.22 136 1.08 0.78 1.32 Comparative Example 2 1.23 128 0.95 0.70 1.18 Comparative Example 3 1.22 142 1.21 0.74 1.45 Comparative Example 4 1.25 121 0.84 0.63 1.05
[0117] As shown in Table 2, the resistivity of Examples 1-3 at 20℃ is 1.21-1.24 μΩ·m, which is generally at a high level with small differences between groups. The temperature coefficients of resistance of Examples 1-3 are 112 × 10⁻⁻⁻⁶. 6 / ℃, 106×10⁻ 6 / ℃ and 101×10⁻ 6 The resistance change rates after energizing at 900℃ for 1000h were 0.53%, 0.48%, and 0.44%, respectively, showing a steady improvement trend with process optimization and no sudden fluctuations.
[0118] Comparative Example 1, lacking the stabilizing effect of composite nano-oxides, showed significant grain coarsening and microstructure evolution after long-term high-temperature energization, with the resistivity change rate increasing to 1.08%. Comparative Example 2, without electroslag remelting, had insufficient alloy purity and compositional uniformity, resulting in decreased oxidation resistance and resistivity stability. Comparative Example 3, employing single-stage aging treatment, exhibited larger precipitate sizes and poor distribution uniformity, leading to higher resistance temperature coefficients and long-term resistivity change rates. Comparative Example 4, due to excessive addition of composite nano-oxides causing particle agglomeration, had a higher resistivity value, but its long-term resistivity stability and thermal cycling stability were lower than those of Examples 1-3.
[0119] Table 3: Mechanical Property Tests
[0120] Example 1 728 30.8 136 27.8 Example 2 742 29.8 142 26.9 Example 3 756 28.9 148 26.1 Comparative Example 1 696 30.1 116 24.6 Comparative Example 2 708 28.7 123 23.8 Comparative Example 3 721 25.6 126 21.7 Comparative Example 4 764 22.8 140 19.8
[0121] As shown in Table 3, the tensile strengths of Examples 1-3 at both room temperature and 900℃ are at a high level, while maintaining good elongation after fracture, indicating that the present invention improves the high-temperature strength of the alloy without significantly sacrificing the material's plasticity. The strength of Example 3 is slightly higher than that of Examples 1 and 2, mainly due to the higher content of composite nanophase, finer grains, and better dispersion of precipitated phases.
[0122] Comparative Example 1 lacks the grain boundary pinning and strengthening effect of composite nano-oxides, resulting in a significant decrease in high-temperature tensile strength. Comparative Example 2, without electroslag remelting, exhibits poor microstructure uniformity and purity, leading to varying degrees of reduction in both strength and plasticity. Comparative Example 3 shows coarsening of the precipitated phase; although the room temperature strength remains at a acceptable level, the plasticity and high-temperature mechanical properties decrease significantly. Comparative Example 4, due to excessive nano-oxide addition, has higher room temperature strength, but its elongation after fracture is significantly reduced, indicating that excessive oxides easily induce local agglomeration and stress concentration, which is detrimental to the material's processing, forming, and long-term service reliability.
[0123] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0124] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-resistivity-stability nickel-chromium alloy material, characterized in that, It includes a nickel-chromium alloy matrix and a composite nanophase dispersed in the nickel-chromium alloy matrix; Based on the mass percentage of the nickel-chromium alloy matrix, the chemical composition of the nickel-chromium alloy matrix is as follows: Cr 18-22%, Al 2.5-4.5%, Mn 1.0-2.0%, Si 0.5-1.5%, Nb 0.3-0.8%, Zr 0.05-0.25%, Y 0.01-0.08%, C 0.02-0.06%, N 0.01-0.03%, S≤0.002%, P≤0.003%, with the balance being Ni and unavoidable impurities; Based on the total mass of the nickel-chromium alloy material, the composite nanophase includes 0.10–0.50% Y2O3-ZrO2 composite nano-oxide particles, as well as Nb, Zr composite carbides and Ni3Al intermetallic compound precipitates in the matrix.
2. The high-resistivity-stability nickel-chromium alloy material according to claim 1, characterized in that, The Nb, Zr composite carbide is (Nb, Zr)C nanocarbide; The total integral number of the composite nanophase in the nickel-chromium alloy matrix is 2 to 6%.
3. The high-resistivity-stability nickel-chromium alloy material according to claim 1, characterized in that, The average particle size of the Y2O3-ZrO2 composite nano-oxide particles is 8-30 nm, and the mass ratio of Y2O3 to ZrO2 is 1:0.5-0.
8.
4. A method for preparing a high-resistivity stable nickel-chromium alloy material as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. Batching and Vacuum Induction Melting: The nickel-chromium alloy matrix is prepared by batching and smelting in a vacuum induction furnace at a temperature of 1550-1600℃ and a vacuum degree of no more than 10Pa. After melting, Al-Ca composite deoxidizer is added for deoxidation treatment, and then it is cast into an electrode rod. S2. Electroslag remelting: The electrode rod obtained in step S1 is subjected to electroslag remelting. The electroslag remelting slag system includes CaF2, Al2O3 and CaO. The melting rate is controlled at 4-6 kg / min during the remelting process to obtain nickel-chromium alloy ingots. S3. Powdering and Mechanical Alloying: The nickel-chromium alloy ingot obtained in step S2 is crushed or milled into alloy powder, and the particle size of the alloy powder is 50-200 μm. The alloy powder is mixed with Y2O3 nanopowder and ZrO2 nanopowder, and then subjected to high-energy ball milling under argon protection to disperse and embed the Y2O3-ZrO2 composite nano-oxide particles into the alloy powder. S4. Hot pressing sintering and hot working: The ball milled powder obtained in step S3 is hot-pressed and sintered in a vacuum or inert atmosphere at a temperature of 1150–1200°C and a pressure of 30–50 MPa. After sintering, the alloy billet is forged and rolled at 1050-1100℃ with a total deformation of not less than 70%. S5. Solution treatment and graded aging: The alloy billet obtained in step S4 is solution treated at 1080–1120°C for 30–60 min and then rapidly cooled. Then, the material undergoes graded aging treatment by holding it at 430–470℃ for 1–3 hours, at 500–540℃ for 3–5 hours, and at 560–600℃ for 1–3 hours in sequence, so that Nb, Zr composite carbides and Ni3Al precipitates are dispersedly precipitated, resulting in a high-resistivity stable nickel-chromium alloy material.
5. The method for preparing the high-resistivity stable nickel-chromium alloy material according to claim 4, characterized in that, In step S1, the amount of Al-Ca composite deoxidizer added is 0.03 to 0.15% of the melt mass; the casting temperature after vacuum induction melting is 1480 to 1520°C, and bottom pouring is adopted.
6. The method for preparing the high-resistivity stable nickel-chromium alloy material according to claim 4, characterized in that, In step S2, the electroslag remelting slag system comprises 50-65% CaF2, 20-35% Al2O3, and 10-20% CaO by mass percentage; the slag material is dried at 650-750℃ for 2-4 hours before electroslag remelting.
7. The method for preparing the high-resistivity stable nickel-chromium alloy material according to claim 4, characterized in that, In step S3, the total amount of Y2O3 nanopowder and ZrO2 nanopowder added is 0.10 to 0.50% of the alloy powder mass; the ball-to-material ratio of the high-energy ball mill is 10 to 20:1, and the ball milling time is 15 to 16 hours. The high-energy ball milling is carried out using a stepped rotation speed: 250-350 rpm in the first stage, 350-450 rpm in the middle stage, and 200-300 rpm in the last stage; the machine is stopped and cooled for 10-20 minutes after each continuous ball milling for 0.5-1.5 hours.
8. The method for preparing the high-resistivity stable nickel-chromium alloy material according to claim 4, characterized in that, In step S5, after the graded aging treatment, the alloy material after graded aging is held at 750-850℃ for 0.5-2 hours and then furnace cooled to increase the proportion of low-energy grain boundaries and coherent twin boundaries in the alloy material and reduce the tendency of continuous precipitates at grain boundaries. The grain boundary controlled annealing treatment is carried out under a strong magnetic field of 8-12T, with the magnetic field direction parallel to the rolling or drawing direction of the alloy material. The heating rate is 3-8℃ / min and the cooling rate is 1-3℃ / min.